Role of Policies and Laws of the Country in the Activities of Exploiting and Using the East Sea - Minh, Do Duc (VNU Journal of Science: Legal Studies; Vol 36 No 2DO - 10.25073/2588-1167/vnuls.4286, 2020)
The paper focuses on research and commentary clarifying some basic theoretical issues about marine policy and law; analyze current situation of policies and laws in the East Sea currently; From there, generalizing matters with methodological significance to identify and confirm the role of national policies and laws on the use and exploitation of the East Sea in the current context . Keywords: role, policy, law, South China sea. References: Kuang-ming Jih-pao (Canton) 24 Nov. 1975 p.2, cited in Samuels. [2] "Oil Drives Territorial Dispute in South China Sea", International Herald Tribunes, 4/24/1995. [3] Multilateralism and the south China sea conflict: Quest for hegemonic stability? [4] I Storey, "China’s Missteps in Southeast Asia: Less Charm, More Offensive" (2010) X China Brief 4. [5] The position of East Vietnam Sea. [6]https://www.academia.edu/28510538/V%E1%BB%8B_th%E1%BA%BF_Bi%E1%BB%83n_%C4%90%C3%B4ng_-_the_position_of_East_Vietnam_Sea._H%E1%BB%99i_ngh%E1%BB%8B_Khoa_h%E1%BB%8Dc_v%C3%A0_C%C3%B4ng_ngh%E1%BB%87_bi%E1%BB%83n_to%C3%A0n_qu%E1%BB%91c_l%E1%BA%A7n_th%E1%BB%A9_V._n%C4%83m_2011._Ti%E1%BB%83u_ban_%C4%90%E1%BB%8Ba_l%C3%BD_%C4%90%E1%BB%8Ba_ch%E1%BA%A5t_v%C3%A0_%C4%90%E1%BB%8Ba_v%E1%BA%ADt_l%C3%BD_Bi%E1%BB%83n._Tr._59-68?email_work_card=view-paper.